2014
DOI: 10.1159/000365884
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Metastatic Bladder Cancer in Both Lungs Treated with Korean Medicine Therapy Alone

Abstract: This case report is aimed to investigate the effects of Korean medicine therapy (KMT) including oral herbal medicine and herb nebulizer therapy in treating metastatic bladder cancer in the lungs. A 74-year-old man was diagnosed with metastatic bladder cancer in both lungs in August 2013. He refused any chemotherapy and was admitted to our hospital in a much progressed state on January 11, 2014. Since then, he was treated with KMT until May 17, 2014. The main oral herbal medicines were Hyunamdan made of heat-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Dietary intakes of flavonol and lignans, multifunctional compounds of plants, have been presented to reduce bladder cancer risk (4). Lee et al, have demonstrated the therapeutic efficacy of herbal medicines in a 74-year-old Korean patient with metastatic bladder cancer, where his pulmonary metastasis was diminished following his herbal treatment (5).…”
Section: Accumulation Of Cytosol Ros and Calcium Signalling Hyperfomentioning
confidence: 99%
“…Dietary intakes of flavonol and lignans, multifunctional compounds of plants, have been presented to reduce bladder cancer risk (4). Lee et al, have demonstrated the therapeutic efficacy of herbal medicines in a 74-year-old Korean patient with metastatic bladder cancer, where his pulmonary metastasis was diminished following his herbal treatment (5).…”
Section: Accumulation Of Cytosol Ros and Calcium Signalling Hyperfomentioning
confidence: 99%
“…YZSJD is a formula contributing to regulate the disorder of human homeostasis, in which the ethanol extract of Scutellaria Barbata D. Don has been revealed to suppress the activation of several colorectal cancer-associated pathways ( 39 ). Cremastra appendiculata tuber , the other type of Cremastrae Pseudobulbus is reported to decrease the metastatic nodules and relieve symptoms of metastatic bladder cancer in the lungs with several herbs ( 40 ). In addition, Yangzheng Xiaoji, a similar formula in which the exact composition is unknown, has been demonstrated to inhibit angiogenesis, thus exhibiting an anticancer effect ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon processing ginseng with heat at 120°C, most peaks of ginsenosides Rb1, Rb2, Rc, and Rd disappeared and the presence of less polar ginsenosides 20(S,R)-Rg3, Rk1, and Rg5 was newly detected [ 8 ]. Lee et al [ 9 ] reported about recurrence control and metastasis decrease in lymph nodes in patients with metastatic breast cancer as well as decrease in the metastatic part of the lung of patients with metastatic bladder infection after ingestion of HAD S and administration of Soram nebulizer solution. Spiam HC is composed of P. ginseng , S. miltiorrhiza , S. officinalis , and A. capillaris Thunberg.…”
Section: Discussionmentioning
confidence: 99%